Aza and oxo Diels–Alder reactions using cis-cyclohexadienediols of microbial origin: chemoenzymatic preparation of synthetically valuable heterocyclic scaffolds. Issue 24 (31st December 2015) - Pazos, Mariana; Martínez, Sebastián; Vila, María Agustina; Rodríguez, Paola; Veiga, Nicolás; Seoane, Gustavo; Carrera, Ignacio
Graphical abstract: Abstract: Aza and oxo Diels–Alder reactions using enantiopure cis -cyclohexadienediols were studied. These dienediols were obtained from the biotransformation of monosubstituted arenes using bacterial dioxygenases (toluene and benzoate dioxygenases). Ethyl glyoxylate and its N -tosyl imine were used as dienophiles to afford the corresponding hetero Diels–Alder bicyclic adducts with excellent regio- and stereoselectivities. Quantum chemical calculations at the B3LYP/6-31+G(d, p) level of theory were performed to rationalize the observed selectivities especially the stereochemical aspects of the cycloadditions. The synthetic importance of these adducts is highlighted for the preparation of enantiopure 2, 2, 3, 4, 5, 6-hexasubstituted piperidine and tetrahydropyran from toluene. Abstract : (1 S, 3 S, 4 R, 7 S, 8 S )-Ethyl-7, 8-isopropylidenedioxy-1-methyl-2-oxabicycle[2.2.2]-5-octen-3-carboxylate: C14 H20 O5 [ α ]D 21  = −51 ( c 0.9, MeOH) Source of chirality: (1 S, 2 R )-3-methylcyclohexa-3, 5-diene-1, 2-diol Absolute configuration: (1 S, 3 S, 4 R, 7 S, 8 S ) Abstract : (1 S, 3 S, 4 R, 7 S, 8 S )-Ethyl-7, 8-isopropylidenedioxy-1-propil-2-oxabicycle[2.2.2]-5-octen-3-carboxylate: C16 H24 O5 [ α ]D 21  = −7.4 ( c 1.1, MeOH) Source of chirality: (1 S, 2 R )-3-propylcyclohexa-3, 5-diene-1, 2-diol Absolute configuration: (1 S, 3 S, 4 R, 7 S, 8 S ) Abstract : (1 S, 3 S, 4 R, 7 S, 8 S )-Ethyl-7, 8-isopropylidenedioxy-1-(acetoxymethyl)-2-oxabicyclo[2.2.2]-5-octen-3-carboxylate: C16 H22 O7 [ α ]D 21  = −23.6 ( c 1.2, MeOH) Source of chirality: (1 S, 2 R )-3-(acetoxymethyl)cyclohexa-3, 5-diene-1, 2-diol Absolute configuration: (1 S, 3 S, 4 R, 7 S, 8 S ) Abstract : (1 S, 3 S, 4 S, 7 R, 8 S )-3-Ethyl-8-methyl-7, 8-isopropylidenedioxy-2-oxabicycle[2.2.2]5-octene-3, 8-dicarboxylate: C15 H20 O7 [ α ]D 21  = +162 ( c 0.5, MeOH) Source of chirality: (1 S, 2 R )-1, 2-dihydroxycyclohexa-3, 5-diene -1-carboxylic acid Absolute configuration: (1 S, 3 S, 4 S, 7 R, 8 S ) Abstract : (2 R, 3 R, 4 S, 5 R, 6 S )-Ethyl-4, 5-dihydroxy-3, 6-bis(hydroxymethyl)-6-methyl-1-tosylpiperidine-2-carboxylate: C21 H31 NO8 S [ α ]D 21  = +17.1 ( c 0.76, MeCN) Source of chirality: (1 S, 2 R )-3-methylcyclohexa-3, 5-diene-1, 2-diol Absolute configuration: (2 R, 3 R, 4 S, 5 R, 6 S ) Abstract : (2 S, 3 S, 4 S, 5 R, 6 S )-2, 5, 6-Tris(hydroxymethyl)-3, 4-isopopilidenedioxy-2-methyltetrahydro-2H-pyran-3, 4-diol: C12 H22 O6 [ α ]D 21  = −45.7 ( c 0.8, MeOH) Source of chirality: (1 S, 2 R )-3-methylcyclohexa-3, 5-diene-1, 2-diol Absolute configuration: (2 S, 3 S, 4 S, 5 R, 6 S )